Implementation of Religious Culture in Developing Students' Interpersonal Intelligence - Muzammil Muzammil; Madina Madina (Universitas Muhammadiyah Enrekang, 2025)
This study examines the implementation of religious culture as a contextual and applicable character-education approach to developing students’ interpersonal intelligence at MTs Darullughah Wal Karomah. Departing from the decline in student morality caused by character programs that remain verbalistic and symbolic, the research positions religious culture as an integrated value ecosystem embedded in daily routines. Through obligatory religious activities, habituation, teacher modelling, and a reward system rooted in Islamic values, students continuously experience moral formation. Employing a qualitative case-study design, data were collected via observation, in-depth interviews, and document analysis. The findings reveal that consistent implementation of religious culture not only deepens students’ spiritual dimension but also enhances interpersonal intelligence by fostering empathy, cooperation, positive communication, and leadership skills. Religious culture thus emerges as an effective, comprehensive, and sustainable character-education strategy that produces tolerant, responsible, and integrity-driven generations.